2022
DOI: 10.3390/jcdd9070209
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular versus Conduction System Pacing after Atrioventricular Node Ablation in Heart Failure Patients with Atrial Fibrillation

Abstract: Conduction system pacing (CSP) modalities, including His-bundle pacing (HBP) and left bundle branch pacing (LBBP), are increasingly used as alternatives to biventricular (BiV) pacing in heart failure (HF) patients scheduled for pace and ablate strategy. The aim of the study was to compare clinical outcomes of HF patients with refractory AF who received either BiV pacing or CSP in conjunction with atrio-ventricular node ablation (AVNA). Fifty consecutive patients (male 48%, age 70 years (IQR 9), left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Changes in clinical NYHA class were significant, and more patients were classified as NYHA I/II in the LBBP group than in the BVP group (median 1.5 vs. 2.0, P = 0.029) at the 6-month follow-up. Consistently, Guo et 41.24 ± 10.56%, P = 0.008) and 1-year follow-ups (49.10 ± 10.43 vs. 43.62 ± 11.33%, P = 0.021). A stable and lower pacing threshold was observed in the LBBP group both at implant (P < 0.001) and the 1-year follow-up (P < 0.001).…”
Section: Comparison Of Left Bundle Branch Pacing With Biventricular P...supporting
confidence: 71%
See 1 more Smart Citation
“…Changes in clinical NYHA class were significant, and more patients were classified as NYHA I/II in the LBBP group than in the BVP group (median 1.5 vs. 2.0, P = 0.029) at the 6-month follow-up. Consistently, Guo et 41.24 ± 10.56%, P = 0.008) and 1-year follow-ups (49.10 ± 10.43 vs. 43.62 ± 11.33%, P = 0.021). A stable and lower pacing threshold was observed in the LBBP group both at implant (P < 0.001) and the 1-year follow-up (P < 0.001).…”
Section: Comparison Of Left Bundle Branch Pacing With Biventricular P...supporting
confidence: 71%
“…Furthermore, we searched studies comparing LBBP with BVP in HF patients with AF and narrow QRS in need of atrioventricular node ablation. Ivanovski et al (41) found shorter-paced QRSd in the LBBP group compared with the BVP group (127.0 ± 13.0 vs. 172.0 ± 13.0 ms, P < 0.001), whereas no significant difference in baseline QRSd was noted. Echocardiographic results showed improved LVEF (P = 0.041) and decreased indexed LV volumes (P = 0.004) in the LBBP group during follow-up, but no significant change was observed in the BVP group (P = 0.916 for LVEF; P = 0.551 for indexed LV volumes).…”
Section: Comparison Of Left Bundle Branch Pacing With Biventricular P...mentioning
confidence: 93%
“…From these studies, 26 were selected for an in-depth review after exclusion of single arm studies. Twenty-one studies, including 17 observational studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 4 RCTs, [31][32][33][34][35] reporting the primary outcomes of interest were included in the final meta-analysis (Figure 1). Of note, the randomized trials by Lustgarten et al 36 and Huang et al 37 were not included in the final analysis as these studies were crossover studies, which were unable to be incorporated into meta-analyses as previously stated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies and guidelines suggest that in patients with reduced LVEF and narrow QRS complex, BVP provides limited benefit ( Moss et al, 2009 ; Tracy et al, 2012 ). Compelling results of applying CSP in patients with PICM, RV pacing upgrading as well as AV node ablation in atrial fibrillation patients are accumulating ( Vijayaraman et al, 2017 ; Cai et al, 2022 ; Huang W. et al, 2022 ; Ivanovski et al, 2022 ). Hence, we expect that CSP may be a better option for primary and upgrading therapy in HF patients who have intact intraventricular conduction but need high RV pacing burden due to bradycardia or AV node ablation.…”
Section: Conduction System Pacing: the Evidence For Clinical Efficacymentioning
confidence: 99%